Suicide in the US Army - Lineberry, Timothy W. (Mayo Foundation, 2012)
Suicide in the US Army is a high-profile public health problem that is complex and poorly understood. Adding to the confusion surrounding Army suicide is the challenge of defining and understanding individuals/populations dying by suicide. Data from recent studies have led to a better understanding of risk factors for suicide that may be specifically associated with military service, including the impact of combat and deployment on increased rates of psychiatric illness in military personnel. The next steps involve applying these results to the development of empirically supported suicide prevention approaches specific to the military population. This special article provides an overview of suicide in the Army by synthesizing new information and providing clinical pearls based on research evidence.